Features of air pollution the cities of the North-Western Black Sea region - Чугай, Ангеліна Володимирівна; Сафранов, Тамерлан Абісалович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Introduction. According to official statistics, regions of Ukraine are characterized by a significant amount of pollutant emissions from stationary sources. But in many areas the dominant contribution to the formation of general levels of air pollution is made by mobile sources. Such regions include the Odessa, Mykolaiv and Kherson regions of the North-Western Black Sea. Regions of the North-Western Black Sea are characterized by a sufficiently high level of technogenic load and have a high recreational potential. This territory is characterized by unique natural resource potential. However, due to the development of urbanization processes, the impact of industrial, transport and agrarian sectors is worsening the overall environmental situation, including the state of the atmospheric air.Review of previous publications. The work of many authors is devoted to the question of the level of air pollution in the cities of the North-Western Black Sea. Most of the works are complex studies of the level of pollution of the regions of Ukraine as a whole. Some works are devoted to the assessment of the technogenic load on the environment of the regions of Ukraine. An analysis of recent research has shown that the vast majority of work is devoted to the regions of Ukraine as a whole. Also, the list of pollutants and the study period are quite limited. Usually, the content of the main pollutants is analyzed. At the same time, the content of specific pollutants is very important in the regions of the North-Western Black Sea in the formation of high levels of atmospheric pollution. Purpose. The purpose of this work is to evaluate and analyze the level of air pollution of individual cities of the North-Western Black Sea over a multi-year period. The complex atmospheric pollution index, which are currently one of the main indicators of atmospheric air quality, were used for the assessment.Results. The level of air pollution in Odessa is in most cases classified as "heavily polluted", Izmail – the only category "slightly polluted" (maximum concentrations in the air pool are marked by the content of formaldehyde). In Mykolayiv maximum concentrations with significant exceedances of the maximum permissible concentration are also noted for formaldehyde content, and the level of atmospheric air pollution was classified as "poorly polluted" – "contaminated". In Kherson, the highest content was observed for substances such as formaldehyde and nitrogen dioxide. The level of pollution, as in the city of Mykolaiv, was classified as "poorly contaminated" – "contaminated".Conclusions. Odessa, by the content of the vast majority of the pollutants, is in the category of cities with high levels of atmospheric pollution, Mykolaiv, Kherson and Izmail – in the category with the permissible level. The results of the study are the basis for the development of environmental recommendations for reducing the emissions of pollutants into the atmospheric air of the region, primarily from mobile sources.